The synergistic effects of nano-curcumin and coenzyme Q10 supplementation in migraine prophylaxis: a randomized, placebo-controlled, double-blind trial. (3rd April 2021) - Parohan, Mohammad; Sarraf, Payam; Javanbakht, Mohammad Hassan; Foroushani, Abbas Rahimi; Ranji-Burachaloo, Sakineh; Djalali, Mahmoud
ABSTRACT: Introduction: Migraine is a disabling neurovascular disorder characterized by increasing levels of pro-inflammatory cytokines and oxidative stress biomarkers. Curcumin and coenzyme Q10 (CoQ10) can exert neuroprotective effects through modulation of inflammation and oxidative stress. The aim of the present study was to evaluate the combined effects of nano-curcumin and CoQ10 supplementation on migraine symptoms and quality of life in migraine patients. Methods: One-hundred men and women (mean age 32 years) with episodic migraine based on the International Headache Society (IHS) criteria participated in this study. The subjects were randomly divided into four groups as (1) combination of nano-curcumin (80 mg) plus CoQ10 (300 mg), (2) nano-curcumin (80 mg), (3) CoQ10 (300 mg) and (4) the control (nano-curcumin and CoQ10 placebo included oral paraffin oil) beside usual prophylactic drugs for 8 weeks. Frequency, severity, duration of headache attacks, the headache diary results (HDR) and headache disability based on migraine-specific questionnaires were assessed at the baseline and end of the study. Results: Ninety-one of 100 patients completed the study. The results showed a significant effect of nano-curcumin and CoQ10 supplementation on frequency, severity, duration of migraine attacks and HDR compared to other groups (All P  < 0.001). Nano-curcumin and CoQ10 group also had better scores in migraine-specific questionnaires at the end of the study compared to other groups (All P  < 0.001). There were no side effects reported by the participants. Conclusions: These findings suggest a possible synergistic effect of nano-curcumin and CoQ10 on clinical features of migraine. Trial registration number: IRCT2017080135444N1.